Problematika Eksekusi Jaminan Gadai terhadap Objek yang Tidak Berada dalam Penguasaan Kreditur menurut Hukum Perdata dan Hukum Islam (Studi Putusan MA Nomor: 600/PK/pdt/2021): Problematika Eksekusi Jaminan Gadai terhadap Objek yang Tidak Berada dalam Penguasaan Kreditur menurut Hukum Perdata dan Hukum Islam (Studi Putusan MA Nomor: 600/PK/pdt/2021) - Fitria Rahmat, Agnis; Astarudin, Tatang; Kamaludin Yusup, Deni (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
Under civil law, the execution of a pledge requires physical possession of the pledged object by the creditor. However, in practice, it is not uncommon for the pledged object to be outside the creditor's control when the debtor defaults. This raises legal issues regarding execution and creditor protection. This study aims to analyze the legal consequences of executing a pledge guarantee when the object is not in the creditor's possession, from the perspective of civil law and Islamic law. The method used is normative legal research with a qualitative approach, based on literature review and analysis of Supreme Court Decision Number: 600/PK/Pdt/2021. The study finds that the absence of possession weakens the executorial power of the pledge, diminishes the creditor’s legal standing, and opens up the potential for disputes with third parties. In Islamic law, possession is also required for a valid rahn contract. Thus, possession is a key element in determining the legitimacy of pledge execution and ensuring legal certainty and protection for creditors.